Solvents and Supporting Electrolytes in the Electrocatalytic Reduction of CO2 - König, Maximilian; Vaes, Jan; Klemm, Elias; Pant, Deepak (iScience, 2019)
Different electrolytes applied in the aqueous electrocatalytic CO2 reduction reaction (CO2RR) considerably influence the catalyst performance. Their concentration, species, buffer capacity, and pH value influence the local reaction conditions and impact the product distribution of the electrocatalyst. Relevant properties of prospective solvents include their basicity, CO2 solubility, conductivity, and toxicity, which affect the CO2RR and the applicability of the solvents. The complexity of an electrochemical system impedes the direct correlation between a single parameter and cell performance indicators such as the Faradaic efficiency; thus the effects of different electrolytes are often not fully comprehended. For an industrial application, a deeper understanding of the effects described in this review can help with the prediction of performance, as well as the development of scalable electrolyzers. In this review, the application of supporting electrolytes and different solvents in the CO2RR reported in the literature are summarized and discussed. [Display omitted] Catalysis; Organic Reaction; Electrochemical Engineering